5(x-2)+3=-(x+4)

Simple and best practice solution for 5(x-2)+3=-(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-2)+3=-(x+4) equation:



5(x-2)+3=-(x+4)
We move all terms to the left:
5(x-2)+3-(-(x+4))=0
We multiply parentheses
5x-(-(x+4))-10+3=0
We calculate terms in parentheses: -(-(x+4)), so:
-(x+4)
We get rid of parentheses
-x-4
We add all the numbers together, and all the variables
-1x-4
Back to the equation:
-(-1x-4)
We add all the numbers together, and all the variables
5x-(-1x-4)-7=0
We get rid of parentheses
5x+1x+4-7=0
We add all the numbers together, and all the variables
6x-3=0
We move all terms containing x to the left, all other terms to the right
6x=3
x=3/6
x=1/2

See similar equations:

| 5(v-7)-8v=-26 | | 82-40x=2 | | 7k+3=4k | | 2x-5x-6.3=14.4 | | 3(d−75)=36 | | 2+9y=7y+2 | | 4x+50=-6x | | 14m+14-9m=3m-18 | | |3-7v|=59 | | 39x+2761x-36=56(50x+56) | | 4g=6g+10 | | 1+8v+7v=7v+1+8v | | 11k=-209 | | x=0.09+0.1x | | -8q+5=-9q | | -18+20s=s+18+17s | | 4-2(3-x)=0.2(6x+10) | | 4y+6=-2(2y+3) | | 10+3a=5 | | -9z=9-6z | | 0=16t^2-48t-2 | | 3(y+4)=60-y | | 13-13+15d=-20+14d | | 11x=24+9x | | X+5x=186 | | -24x=44 | | 2(4x-3)-8=4+2x | | 7z+5+(-19)=52 | | -8h+8=-10h | | -4.9t^2+19.6t+90=0 | | (7t-2)+4(3t+1)=-3(6-3t) | | 18v+4-7v=-5+10v |

Equations solver categories